Climate Change Perception, Climate Change Anxiety, & Pro-environmental Behaviors of Tertiary Students - Fuentes, Lance Cary D. (Technium Social Sciences Journal, 2024)
The Philippines is one of the most climate change-vulnerable countries in the world. As the climate crisis pose physical and mental threats, it is crucial to understand the factors affecting environmental behavior. However, local studies on the role of Psychology in encouraging pro-environmental behaviors (PEB) appear to be few in the Philippines. This study was designed to determine the level and the predictive ability of climate change perception (CCP) and climate change anxiety (CCA) on PEB. A stepwise regression analysis was used on data collected from 430 stratified randomly sampled tertiary students in Bacolod city, Philippines who completed the Climate Change Perception Scale, Climate Change Anxiety Scale, and Pro-environmental Behavior Scale. Results showed that the parsimonious model that include climate change anxiety (t=13.585, p=.000) and climate change perception (t=6.409, p=.000) significantly predicted pro-environmental behaviors F(1, 426) = 115.284, p < .001, adj. R2 = .349. Further, findings indicate that 34.9% of the variance in the pro-environmental behaviors can be explained by the model. In conclusion, when tertiary students experience higher levels of climate change anxiety and perceive climate change as a significant threat, they are more likely to engage in pro-environmental behaviors. Results suggest a need for further research in determining other factors that predict PEB. This study contributes to the scarce literature on Environmental Psychology in the country.